Integration of Islam and Science in Islamic Education - Triyono; Izzah Nur Aida Zur Raffar (UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
This article aims to discuss the paradigm of scientific integration between Islam and science. Integration, which has been based on scientific ideas, should have started with integration based on divine ideas. Therefore, the main focus of this paper is how the basic framework of thinking in the integration of Islam and science is based on the idea of divinity, its application in the world of education and the challenges that must be faced with the integration of Islam and science based on the idea of divinity. To answer these problems, the article was designed using the literature review method. Finally, this article sees that the basic idea of integrating science and science must be based on God. This idea is a concrete theoretical solution to immediately realize the integration of science between Islam and science which has long been echoed but is still difficult to implement. Integration that emphasizes the embodiment of divinity in terms of the praxis of knowledge and science, does not bring science into Islamic science. Concretely, in the world of education, this embodiment can be seen from the goals set by an institution in organizing it.